Variables determining the effects of delay in reinforcement, - Ferster, C. B. (1965)
Procedures were discovered for maintaining a small fixed-ratio performance under 24-hr delay in reinforcement, by appropriate manipulation of the length of delay, amount of food delivered, and size of the fixed ratio. Other experiments showed that (1) the parameters discovered in the first experiment could produce the same result without the complex history of the first procedures; (2) the same parameters of the delayed-reinforcement procedure could maintain an explicit chain of responses; (3) gradual increase in the delay in reinforcement from small to large values was not a necessary condition for achieving the major result, if large amounts of food were delivered as reinforcement and all of the behaviors were first under good control of the relevant stimuli with short delays.